The "Green Doctor" Initiative: Ethical Healthcare in the Age of Medical Commercialization (International Journal of Scientific Research and Management (IJSRM), 2024)
The "Green Doctor" initiative represents a groundbreaking shift in global healthcare systems, aiming to prioritize ethical, compassionate, and patient-centered care in an era of increasing commercialization. Proposed by Professor Reza Ghalamghash, the "Green Doctor" concept focuses on the moral obligations of healthcare professionals to provide care that transcends financial considerations and commercial pressures. This innovative model emphasizes the humanistic aspects of medicine, where physicians are encouraged to focus on patients’ holistic well-being, mental and emotional health, and equitable access to care. In the face of rising healthcare costs, systemic inequities, and ethical dilemmas posed by profit-driven models, the "Green Doctor" approach is particularly timely. This article explores the philosophical foundation of the "Green Doctor" concept, its implications for healthcare systems around the globe, and its potential to drive meaningful change in public health policy and medical practices. Through a detailed exploration of real-world case studies, the article delves into how this model is being adopted in different healthcare settings, examining its efficacy in enhancing patient outcomes, promoting healthcare equity, and reshaping the relationship between doctors and their patients. Additionally, the article discusses the structural challenges faced by healthcare providers in implementing this approach, including financial constraints, regulatory hurdles, and the need for institutional support. It also highlights the role of technology in facilitating the "Green Doctor" model, particularly through the use of telemedicine, digital health platforms, and AI-driven diagnostics, which allow doctors to extend care to underserved populations while maintaining a patient-centered focus. Finally, the article assesses the future of the "Green Doctor" initiative in the context of evolving global healthcare challenges, offering insights into how it could serve as a sustainable model for ethical healthcare in the 21st century.